Poststructuralist Discourse Analysis - Angermuller, J. author. aut Link
IX, 163 p.
Keywords: This book presents developments of discourse analysis in France and applies its tools to key texts from five theorists of structuralism: Lacan, Althusser, Foucault, Derrida and Sollers. It pays special attention to enunciative pragmatics as a poststructuralist approach which analyzes the discursive construction of subjectivity.